2019
DOI: 10.3390/cells8121651
|View full text |Cite
|
Sign up to set email alerts
|

Heart Failure with Reduced Ejection Fraction (HFrEF) and Preserved Ejection Fraction (HFpEF): The Diagnostic Value of Circulating MicroRNAs

Abstract: Circulating microRNAs offer attractive potential as epigenetic disease biomarkers by virtue of their biological stability and ready accessibility in liquid biopsies. Numerous clinical cohort studies have revealed unique microRNA profiles in different disease settings, suggesting utility as markers with diagnostic and prognostic applications. Given the complex network of microRNA functions in modulating gene expression and post-transcriptional modifications, the circulating microRNA landscape in disease may ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 78 publications
1
34
0
1
Order By: Relevance
“…In our analysis, hsa-miR-106a-5p , hsa-miR-193b-3p , hsa-miR-193b-5p , hsa-miR-191-5p and hsa-miR-660-5p showed significantly differential expression between the low- and high-risk group. Existing literature revealed that these miRNAs were associated with several mechanisms of potential HF [38] , [39] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our analysis, hsa-miR-106a-5p , hsa-miR-193b-3p , hsa-miR-193b-5p , hsa-miR-191-5p and hsa-miR-660-5p showed significantly differential expression between the low- and high-risk group. Existing literature revealed that these miRNAs were associated with several mechanisms of potential HF [38] , [39] .…”
Section: Discussionmentioning
confidence: 99%
“…For example, HF biomarker-NT-proBNP was increased moderately in HFpEF and showed poor predictive value for HFpEF [39] . A study showed that biomarker panels of microRNAs demonstrated higher discriminative power for distinguishing HFpEF compared to the result using plasma NT-proBNP levels alone [38] . Additionally, studies of HFpEF from the 1980s to the present have shifted from the perspective of mechanistic understanding to multi-organ focused disease study [61] including pulmonary arterial hypertension, obesity and metabolic diseases, vascular stiffness, chronological impotence, skeletal muscle disease, and renal insufficiency [62] .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, numerous studies have been conducted concerning the heterogeneous and complex syndrome known as heart failure (HF). In particular, heart failure with reduced ejection fraction (EF) and heart failure with preserved ejection fraction (HFpEF) were defined [100][101][102][103]. The majority of the population is affected by heart failure with preserved ejection fraction, prevalent in the ageing population.…”
Section: The Potential For N-3 Pufas Supplementation In Heart Failurementioning
confidence: 99%
“…Half of heart failure patients display reduced left ventricular ejection fraction, termed HFrEF (heart failure with reduced ejection fraction), and the other half present preserved left ventricular ejection fraction, termed HFpEF (heart failure with preserved ejection fraction) [2,3]. Most of the available therapies for heart failure were developed to treat HFrEF, but not HFpEF [2][3][4][5]. Considering these are diseases with different pathophysiology, there is still uncertainty about the effectiveness of HFrEF interventions to treat HFpEF patients.…”
Section: Introductionmentioning
confidence: 99%